Violence Against Women: Experiences of Eritrean Refugee Women in Britain - Tsegay, Samson Maekele (Violence against women, 2025)
There is a dearth of research on violence against women and girls among refugees, particularly in their host countries. Therefore, informed by a feminist theoretical framework and semistructured interviews, this study explores violence against women focusing on Eritrean refugee women's experiences in Britain. The findings suggest that Eritrean refugee women experience various types of violence, which have short- and long-term effects on their lives. Moreover, the data indicate that host and origin countries’ socioeconomic and cultural situations shape the experiences of refugee women. The research aims to better understand violence against women among refugees and thus improve refugee women's experiences.